A Turner Syndrome Patient Carrying a Mosaic Distal X Chromosome Marker - Roberto L. P. Mazzaschi; Juliet Taylor; Stephen P. Robertson; Donald R. Love; Alice M. George (Case Reports in Genetics)
A skin sample from a 17-year-old female was received for routine karyotyping with a set of clinical features including clonic seizures, cardiomyopathy, hepatic adenomas, and skeletal dysplasia. Conventional karyotyping revealed a mosaic Turner syndrome karyotype with a cell line containing a small marker of X chromosome origin. This was later confirmed on peripheral blood cultures by conventional G-banding, fluorescence in situ hybridisation and microarray analysis. Similar Turner mosaic marker chromosome cases have been previously reported in the literature, with a variable phenotype ranging from the mild “classic” Turner syndrome to anencephaly, agenesis of the corpus callosum, complex heart malformation, and syndactyly of the fingers and toes. This case report has a phenotype that is largely discordant with previously published cases as it lies at the severe end of the Turner variant phenotype scale. The observed cytogenetic abnormalities in this study may represent a coincidental finding, but we cannot exclude the possibility that the marker has a nonfunctioning X chromosome inactivation locus, leading to functional disomy of those genes carried by the marker.